Abreviasi Nama Dagang Badan Usaha Milik Negara (BUMN) di Indonesia - Suryani, Diana Sri (Crises on Languages and Literature, 2024)
The abbreviation is often found in naming institutions in Indonesia. This research is descriptive-qualitative. This research aims to identify the forms and patterns of abbreviations in naming State-Owned Enterprises (BUMN) in Indonesia. The data collection method in this research is by observing and note-taking techniques. The data in this research are the trade names of State-Owned Enterprises (BUMN), which are undergoing a shortening process. The data was analyzed using the high method and the theory regarding Indonesian abbreviations by Kridalaksana. This research found that the abbreviations in BUMN trade names are abbreviations, acronyms, and fragments. The pattern for forming BUMN trade name abbreviations is by retaining the first letter of each component, retaining the first letter with the deletion of conjunction, retaining the first two letters, retaining the first three letters, retaining syllables, retaining letters and syllables, and abbreviating syllables.